“Refined” Decrees, Diplomas of “Elegant Style,” and “Artistic” Letters in Ottoman Turkish: Between the “Insha” Rules of Writing and Diplomatic and Paleographic Features - Kolaj Ristanović, Irena D. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
For several centuries, the Ottoman state upheld a dual legal tradition, combining Islamic law (sharia) with the sultan’s law (kanun), while recognizing Islam as the official religion of the Empire. Documents issued by both central and local administrations of the Ottoman Empire, grounded in legal regulations, displayed a distinctive structure. At the same time, various manuscripts followed the insha (inşa) rules of writing, which had developed within the chanceries of the administrative, executive, and judicial branches of the Ottoman state apparatus. The structure of these documents and manuscripts, conceived as specific forms of letters, provides valuable evidence for multiple scholarly disciplines. Accordingly, this structure is studied within Ottoman diplomatics, paleography, and auxiliary historical sciences. This paper seeks to emphasize their multifaceted significance by examining the content and structure of such writings, with attention to early practices of their preservation. The study adopts an interdisciplinary approach, drawing on sources of both Serbian and Ottoman provenance, alongside relevant scholarly literature.
Keywords: document; letter; insha (inşa); diplomatics; paleography; Ottoman